2019
DOI: 10.1177/0018578719893376
|View full text |Cite
|
Sign up to set email alerts
|

Y-Site Compatibility of Intravenous Levetiracetam With Commonly Used Critical Care Medications

Abstract: Purpose: Levetiracetam is an antiepileptic medication commonly used in critical care areas for seizure treatment or prophylaxis. Compatibility data of levetiracetam with other critical care medications are limited, which can make administration challenging. This study aims to assess the physical Y-site compatibility of intravenous levetiracetam with some other commonly used critical care medications. Methods: Y-site administration was simulated by independently mixing levetiracetam with each of 11 selected med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Studies reported that pH changes of intravenous drug solution within the range of 0.2 to 1.0, the solution was stable and compatible [19][20][21][22]. Dotson et al defined physical incompatibility as a pH value of no more than 10% change from baseline (0 hour) after 48 hours [15].…”
Section: Plos Onementioning
confidence: 99%
“…Studies reported that pH changes of intravenous drug solution within the range of 0.2 to 1.0, the solution was stable and compatible [19][20][21][22]. Dotson et al defined physical incompatibility as a pH value of no more than 10% change from baseline (0 hour) after 48 hours [15].…”
Section: Plos Onementioning
confidence: 99%
“…Compatibility was based on Trissel's criteria, defined as: (a) Absence of visible or electronically determined particulates, haziness or turbidity, frank precipitation, colour or evolution of a gas; (b) all drug components in the test samples were found to be chemically stable (less than 10% loss of intact drug) for at least 24 h under the test conditions, or for the entire study period under the test conditions if the study period was less than 24 h 16,40,41 …”
Section: Resultsmentioning
confidence: 99%
“…Until now, no official compendium or harmonized methodology has been established to evaluate PNA stability. Based on the research data and our own experience, we used different analytical methods which allowed us to detect changes in the physicochemical properties of VPA-RTU samples [15][16][17][18]31,32,[39][40][41][42][43][44][45][46]. Despite the duration of the VPA infusion of approximately a few hours and of the PNA from 16 to 24 h, the real-time contact in a common line of Y-site connector lasted only a few minutes.…”
Section: Discussionmentioning
confidence: 99%